Adipose-derived stem cells using fibrin gel as a scaffold enhances post-hepatectomy liver regeneration - Hiroki Imamura; Yoshito Tomimaru; Shogo Kobayashi; Akima Harada; Shunbun Kita; Kazuki Sasaki; Yoshifumi Iwagami; Daisaku Yamada; Takehiro Noda; Hidenori Takahashi; Daiki Hokkoku; Takeshi Kado; et al. (Scientific Reports)
Abstract We investigated the potential of adipose-derived stem cells (ADSCs) in preventing post-hepatectomy liver failure, emphasizing the necessity of direct administration using a scaffold. A fibrin gel scaffold was employed for ADSCs (gelADSC) to assess their therapeutic impact on liver regeneration in both in vitro and in vivo settings. Experiments were conducted on C57BL/6 mice with normal livers and those with chronic hepatitis. We also explored the role of extracellular vesicles (EVs) secreted by ADSCs in conjunction with fibrin gel. GelADSC showed sustained release of hepatocyte growth factor, vascular endothelial growth factor, and stromal cell–derived factor 1 for at least 7 days in vitro. In vivo, gelADSC significantly enhanced postoperative liver regeneration by upregulating the cell cycle and fatty acid oxidation in both normal and chronically hepatitis-affected mice. The therapeutic effects of gelADSC were potentially favorable over those of intravenously administered ADSCs, especially in mice with chronic hepatitis. Increased EV secretion associated with fibrin gel use was significantly linked to enhanced liver regeneration post-surgery through the promotion of fatty acid oxidation. The findings underscore the enhanced therapeutic potential of gelADSC, particularly in the context of chronic hepatitis, possibly compared to intravenous administration.